Olive oil bioactive compounds increase body weight, and improve gut health and integrity in gilthead sea bream (Sparus aurata). Issue 3 (1st March 2017) - Gisbert, Enric; Andree, Karl B.; Quintela, José C.; Calduch-Giner, Josep A.; Ipharraguerre, Ignacio R.; Pérez-Sánchez, Jaume
Abstract: An olive oil bioactive extract (OBE) rich in bioactive compounds like polyphenols, triterpenic acids, long-chain fatty alcohols, unsaturated hydrocarbons, tocopherols and sterols was tested (0, 0·08, 0·17, 0·42 and 0·73 % OBE) in diets fed to sea bream ( Sparus aurata ) (initial weight: 5·4 (sd 1·2) g) during a 90-d trial (four replicates). Fish fed diets containing 0·17 and 0·42 % OBE were 5 % heavier (61·1 (sd 1·6) and 60·3 (sd 1·1) g, respectively) than those of the control group (57·0 (sd 0·7) g), although feed conversion ratio and specific feed intake did not vary. There were no differences in lipid peroxidation (LPO) levels, catalase, glutathione reductase and glutathione S -transferase activities in the intestine and liver, although there was a tendency of lower intestinal and hepatic LPO levels in fish fed OBE diets. No differences in villus size were found among treatments, whereas goblet cell density in the control group was on average14·3 % lower than in fish fed OBE diets. The transcriptomic profiling of intestinal markers, covering different biological functions like (i) cell differentiation and proliferation, (ii) intestinal permeability, (iii) enterocyte mass and epithelial damage, (iv) IL and cytokines, (v) pathogen recognition receptors and (vi) mitochondria function, indicated that among the eighty-eight evaluated genes, twenty-nine were differentially expressed (0·17 % OBE diet), suggesting that the additive has the potential of improving the condition and defensive role of the intestine by enhancing the maturation of enterocytes, reducing oxidative stress, improving the integrity of the intestinal epithelium and enhancing the intestinal innate immune function, as gene expression data indicated.